2004
DOI: 10.1007/s00432-003-0508-9
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly CHOP or THP-COP regimens in the treatment of newly diagnosed aggressive non-Hodgkin?s lymphoma

Abstract: Although both regimens effectively treated those patients with favorable prognostic factors, neither was satisfactory for treating those with poor prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
3
32
1
Order By: Relevance
“…As a minimum requirement, intensive chemotherapy and palliative therapy should be considered for the treatment of elderly patients aged 80 years or older who have DLBCL. Regarding patients who have DLBCL who are younger than 80 years of age, and have favourable prognostic factors, the CR/CRu, survival, and adverse effects in this study are no worse that those in patients younger than 70 years of age in our experience [6]. Thus, intensive chemotherapy should be considered in order to achieve better outcomes for both elderly patients with DLBCL aged between 70 and 80 years, and those patients with DLBCL who are younger than 70 years.…”
Section: Haematological Toxicitycontrasting
confidence: 55%
See 1 more Smart Citation
“…As a minimum requirement, intensive chemotherapy and palliative therapy should be considered for the treatment of elderly patients aged 80 years or older who have DLBCL. Regarding patients who have DLBCL who are younger than 80 years of age, and have favourable prognostic factors, the CR/CRu, survival, and adverse effects in this study are no worse that those in patients younger than 70 years of age in our experience [6]. Thus, intensive chemotherapy should be considered in order to achieve better outcomes for both elderly patients with DLBCL aged between 70 and 80 years, and those patients with DLBCL who are younger than 70 years.…”
Section: Haematological Toxicitycontrasting
confidence: 55%
“…Pirarubicin (tetrahydropyranyl adriamycin: THP), a derivative of doxorubicin (DOX), is a new anthracycline that has been reported to be less cardiotoxic than DOX [3][4][5]. Accordingly, a THP-COP regimen [6] composed of THP, cyclophosphamide (CPA), vincristine (VCR), and prednisolone (PSL) has been administered for the treatment of NHL in elderly patients [7][8][9]. Recently, the Japanese Clinical Study Group of THP Lymphomas in the Elderly (JGTLE) reported on the efficacy of a THP-COP regimen based on its large-scale, multicenter trial [9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, elderly patients with NHL have been treated (Kitamura and Takaku 1990;Niitsu and Umeda 1997;Mori et al 2005) with a THP-COP regimen (Tsurumi et al 2004) comprising THP, cyclophosphamide (CPA), vincristine (VCR), and prednisolone (PSL).…”
Section: Introductionmentioning
confidence: 99%
“…The THP-COP regimen included THP, which is an anthracycline derivative of DOX with reportedly lower cardiotoxicity than DOX (Miller and Salewski 1994;Takagi and Oguro 1987). Our prospective randomized study found no signiWcant diVerences in remission and survival rates between CHOP and THP-COP therapy (Tsurumi et al 2004). Patients aged ¸70 years were assigned to receive six cycles of THP-COP therapy, which is often applied to elderly patients with NHL (Tsurumi et al 2007).…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Patients in group A aged <70 years received eight cycles of CHOP or THP-COP therapy without rituximab (Tsurumi et al 2004). Each regimen consisted of cyclophosphamide (CPA; 750 mg/m 2 i.v.…”
Section: Treatment Strategiesmentioning
confidence: 99%